2014
DOI: 10.1039/c4gc00853g
|View full text |Cite
|
Sign up to set email alerts
|

t-BuXPhos: a highly efficient ligand for Buchwald–Hartwig coupling in water

Abstract: A highly efficient, eco-friendly N-arylation was disclosed outspreading perspectives in green Buchwald–Hartwig reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 67 publications
0
47
0
Order By: Relevance
“…Aminations with secondary, and perhaps more importantly, primary amines under these micellar conditions were found to afford unacceptable yields of the anticipated C−N bond‐containing products. More recent work, however, has shown that by altering the ligand, in this case from cBRIDP to t BuXPhos, together with a change from the catalyst precursor [PdCl(allyl)] 2 to the cinnamyl analog [PdCl(cinnamyl)] 2 led to high yields of the targeted products of amination in water at 50 °C (Scheme ) . These updated conditions proved to be quite general, being applied to a broad range of amines and primary benzamides suggesting that these modified conditions are likely to give better results than those from prior art.…”
Section: Spotlight On Pd Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Aminations with secondary, and perhaps more importantly, primary amines under these micellar conditions were found to afford unacceptable yields of the anticipated C−N bond‐containing products. More recent work, however, has shown that by altering the ligand, in this case from cBRIDP to t BuXPhos, together with a change from the catalyst precursor [PdCl(allyl)] 2 to the cinnamyl analog [PdCl(cinnamyl)] 2 led to high yields of the targeted products of amination in water at 50 °C (Scheme ) . These updated conditions proved to be quite general, being applied to a broad range of amines and primary benzamides suggesting that these modified conditions are likely to give better results than those from prior art.…”
Section: Spotlight On Pd Catalysismentioning
confidence: 99%
“…[67] These and several other fascinating and intriguing discoveries, as detailsa ssociated with the various topics in this review,a re presented herein. There are also many "firsts" in micellar catalysis appliedt oo rganic synthesis, such as:1 )new ligands designed for applications based on micellar catalysis in water; [17,19,23,38] 2) ppm level metal-catalyzed processes; [27,39,50,54,56] 3) new heterogeneous nanoparticles that catalyze av ariety of important, commonly utilized reactions; [27,39,49,50] 4) new hybrid micellar derivatives that incorporate reagents within their structure; [25,49,67,69] 5) industrially important developments on the use of micelles influenced by the presenceo fc o-solvents; [75][76][77][78] and 6) examples of one-pot tandem processes enabled by micellar conditions. [27,81,82,85,88,89] These and several relatede xamples from just the past few years further documentt he potentialo ft his blossoming technology,i llustrating new synthetic chemistry that is sustainable, environmentally responsible, and acknowledges that chemistry as practiced today must be changedt ob ei ns tep with the laws of Nature.…”
Section: What'snew In Micellar Catalysis?mentioning
confidence: 99%
“…Recently, our group further investigated the Buchwald–Hartwig reaction, as the formation of C−N bonds is one of the most useful reaction types in medicinal chemistry and materials science . Thus, we reported a universal catalytic system for Buchwald–Hartwig reactions under micellar conditions . However, the industrial use of these methods may be limited by the high cost, scarcity, and toxicity of palladium.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 The catalyst loading can be greatly reduced and the recyclability of the reaction medium further helps in reducing the environmental impact of several common organic reactions. 29,30 As the Buchwald-Hartwig reaction is also reported to be particularly efficient under appropriate micellar conditions, [46][47][48] we decided to merge micellar amination and cyclization under Wang's conditions 23 in a new protocol for the preparation of unsymmetrically fluorinated acridine derivatives.…”
Section: Feature Syn Thesismentioning
confidence: 99%
“…46,48 The group of Christophe Salomé and Martine Schmitt later made an extensive screening of the possible catalytic systems, concluding that [(cinnamyl)PdCl] 2 /t-BuXPhos is advantageous both in terms of generality and of performance of the reaction over different nitrogen-containing nucleophiles. 47,48…”
Section: Feature Syn Thesismentioning
confidence: 99%